Seasonal changes in photosynthesis and photoprotection in a Quercus ilex subsp. ballota woodland located in its upper altitudinal extreme in the Iberian Peninsula - Corcuera, L; Morales, F; Abadía, A; Gil-Pelegrín, E (Tree Physiology, 2005)
Quercus ilex L. subsp. ballota (Desf.) Samp., a Mediterranean evergreen species growing in a continental Mediterranean climate, did not experience water stress and showed greater sensitivity to winter stress than to summer stress over a 12-month period. Net CO2 assimilation rates and photosystem II (PSII) efficiency decreased markedly during the cold months and recovered completely in spring. Lutein, neoxanthin and β-carotene to chlorophyll (Chl) molar ratios all showed the same trend throughout the year, increasing from September to March. This increase was a result of increases in carotenoid concentrations, because Chl concentration per unit leaf area remained stable, and was higher at the end than at the beginning of the first growing season. Lutein-epoxide was a minor component of the total lutein pool. Thermal energy dissipation and non-photochemical quenching (NPQ) were associated with the de-epoxidated forms of the xanthophyll cycle pigments in the warm months. Photosynthetic rates decreased slightly at midday in summer. These changes were accompanied by decreases in maximum potential PSII efficiency (which recovered during the night), actual and intrinsic PSII efficiencies, photochemical quenching and increases in NPQ. Overall, our data indicate down-regulation of photosynthesis during the summer. The diurnal de-epoxidation of violaxanthin to antheraxanthin and zeaxanthin occurred throughout the year, except in January. Antioxidant enzymatic activity increased in the winter months, especially during the coldest months, highlighting its key role in photoprotection against photo-oxidation. Structural and functional modifications protected PSII from permanent damage and allowed 1-year-old leaves to photosynthesize at high rates when temperatures increased in spring.
10.1093/treephys/25.5.599
Keywords: antioxidant enzymatic activity; chlorophyll fluorescence; photosynthetic pigments; summer stress; winter stress

The effect of low temperatures on the photosynthetic apparatus of Quercus ilex subsp. ballota at its lower and upper altitudinal limits in the Iberian peninsula and during a single freezing-thawing cycle - Corcuera, L; Morales, F; Abadía, A; Gil-Pelegrín, E (Trees, 2004)
We investigated the response of the photosynthetic apparatus during an episode of extreme low winter temperature in Quercus ilex subsp. ballota (Desf.) Samp., a typical Mediterranean evergreen species in the Iberian peninsula. Both plants in a woodland located at high altitude (1,177 m. a.s.l.) and potted plants obtained from acorns of the same populations grown at low altitude (225 m. a.s.l.) were analyzed. Net CO2 assimilation rate was negative and there was a marked decrease in photosystem II (PSII) efficiency during winter in leaves of the woodland population (high altitude individuals). These processes were accompanied by increases in nonphotochemical quenching (NPQ) and in the de-epoxidated carotenoids within the xanthophyll cycle, mechanisms aimed to dissipate excess energy. In addition, these deepoxidated carotenoids were largely preserved during the night. There was no chlorophyll bleaching during the winter, which suggests that leaves were not experiencing photoinhibitory damage. In fact, the net photosynthetic rate and the PSII efficiency recovered in spring. These changes were not observed, or were much more reduced, in individuals located at lower altitude after a few frosts. When the response to rapid temperature changes (from 20°C to −5°C and from −5°C to 20°C) was studied, it was found that the maximum potential PSII efficiency was fairly stable, ranging from 0.70 to 0.75. The rest of the photosynthetic parameters measured, actual and intrinsic PSII efficiency, photochemical and NPQ, responded immediately to the changes in temperature and, also, the recovery after cold events was practically immediate.
Keywords: chlorophyll fluorescence; Holm oak; photochemical and non-photochemical quenching; photoprotection; photosystem ii efficiency

Trichomes and photosynthetic pigment composition changes: responses of Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L. to Mediterranean stress conditions - Morales, F; Abadía, A; Abadia, J; Montserrat, G; Gil-Pelegrín, E (Trees, 2002)
Sun and shade leaves of two Mediterranean Quercus species, Quercus ilex subsp. ballota (Desf.) Samp. and Quercus coccifera L., were compared by measuring leaf optical properties, photosynthetic pigment composition and photosystem II efficiency. The presence of trichomes in the adaxial (upper) leaf surface of Q. ilex subsp. ballota seems to constitute an important morphological mechanism that allows this species to maintain a good photosystem II efficiency during the summer. Q. coccifera has almost no trichomes and seems instead to develop other physiological responses, including a smaller light-harvesting antenna size, higher concentrations of violaxanthin cycle pigments and a higher (zeaxanthin + antheraxanthin)/(violaxanthin + antheraxanthin + zeaxanthin) ratio. Q. coccifera was not able to maintain a good photosystem II efficiency up to the end of the summer. In Q. ilex subsp. ballota leaves, natural loss or mechanical removal of adaxial-face leaf trichomes induced short-term decreases in photosystem II efficiency. These changes were accompanied by deepoxidation of violaxanthin cycle pigments, suggesting that the absence of trichomes would trigger physiological responses in this species. Our data have revealed different patterns of response of Q. ilex subsp. ballota and Q. coccifera facing the stress conditions prevailing in the Mediterranean area.
Keywords: adaxial epidermis; photoprotection; Quercus; Trichomes

Influencia del clima en el crecimiento longitudinal y radial de Q. ilex ssp. ballota L. y Q. faginea Lam. EN EL SISTEMA IBERICO ARAGONES - Corcuera, L; CAMARERO, J J; Gil-Pelegrín, E (III Congreso Forestal Español, 2001)
Climate influence (precipitation and temperature) on primary growth (annual growth length) and secondary growth (ring width and ring surface) of Quercus ilex ssp. ballota L. (evergreen and diffuse-porous species) and Q. faginea Lam. (decidious and ring-porous species) is studied. Samples were taken from a coppice in Sierra de Santa Cruz, Cubel, Zaragoza. Both species show lesser longitudinal and radial growth in drought years. A positive and significant relationship between precipitation and secondary growth and a negative and significant relationship between high summer temperatures and secondary growth were observed. Primary and secondary growth in 1993 and previous years mirror foliage desiccation of Q. ilex in 1993.
Keywords: climate; primary growth; Q. faginea; Q. ilex ssp. ballota; secondary growth